Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Review: 12

Answer

x=6

Work Step by Step

Simplifying 4x + 2(x + 3) = 42 Reorder the terms: 4x + 2(3 + x) = 42 4x + (3 * 2 + x * 2) = 42 4x + (6 + 2x) = 42 Reorder the terms: 6 + 4x + 2x = 42 Combine like terms: 4x + 2x = 6x 6 + 6x = 42 Solving 6 + 6x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 42 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 42 + -6 6x = 42 + -6 Combine like terms: 42 + -6 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.